The role of smart cities to promote smart governance in municipalities - Vuyani Goodman LANGA; Reckson Dovhani THAKHATHI (Smart Cities and Regional Development Journal)
The main focus of this paper is to provide a contextualized reflection about what smart cities are and their primary contribution in promoting smart governance.